1951
DOI: 10.1161/01.cir.4.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Cheyne-Stokes Respiration in Patients with Cardiac Enlargement and Prolonged Circulation Time

Abstract: A study has been made of arterial blood changes during the respiratory cycle in patients with cardiac enlargement, prolonged circulation time, and Cheyne-Stokes breathing. In these patients, Cheyne-Stokes breathing appeared to depend upon the delay in passage of blood from the lungs to the arterial chemoreceptors and respiratory center. This delayallowed cyclic over- and underventilation. There was little or no central nervous system depression. In contrast, one case of Biot's breathing is presented as an exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
1
1

Year Published

1962
1962
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 7 publications
4
27
1
1
Order By: Relevance
“…b) The absence of significant arterial oxygen unsaturation (except in Cases 5, 8, and 9) is in agreement with other reports (3,5,7). None of the patients appeared cyanotic during any portion of the respiratory cycle, nor was clubbing found.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…b) The absence of significant arterial oxygen unsaturation (except in Cases 5, 8, and 9) is in agreement with other reports (3,5,7). None of the patients appeared cyanotic during any portion of the respiratory cycle, nor was clubbing found.…”
Section: Discussionsupporting
confidence: 91%
“…There is, however, evidence that mild anoxemia potentiates the effects of Paco2 on the carotid body or medullary receptors (9,10). c) Previous studies have shown varying degrees of hypocapnea (3,7). In the present study analysis of end-tidal gas reveals a lowered PACO2 at all times.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In chronic disease states such as HF, a potential contributor to the alterations in matching between the peripheral feedback and regulatory activity of the CNS includes circulatory delay 8,9,20,32,33 . When blood transport slows (i.e.…”
Section: Conceptual Model For Control Of Periodic Breathingmentioning
confidence: 99%
“…This breathing abnormality, characterized by alternating periods of hyperpnoea and hypopnoea or apnoea, is one form of central apnoea and appears to be much more common during sleep (central sleep apnoea (CSA)) than wakefulness [3]. The main mechanism responsible for Cheyne-Stokes respiration is believed to be a phase delay between peripheral and central chemoreceptors due to prolonged circulation time [4]. This phase delay would promote unstable respiratory control, leading to periodic respiration with alternating hyperpnoea and hypopnoea or apnoeas.…”
mentioning
confidence: 99%